(untitled) (Journal of Interdisciplinary Insights, 2026)
The history of broadcasting development in Myanmar has so far been divided into four stages: the colonial dependency stage (1938-1948), the Cold War confrontation stage (1948-1988), the military government monopoly stage (1988-2010), and the digital sovereignty stage (2010-2025). Throughout these four stages, the control of communication has always been the core concern, but each stage has its own focus. The first stage was dominated by the transplantation of colonial technologies, establishing an attached broadcasting system, and the content and form of communication were deeply influenced by colonial ideology; the second stage was oriented towards political propaganda and geopolitical strategy, with broadcasting becoming a propaganda tool for the great powers’ competition during the Cold War, and the media becoming a weapon in political games, presenting characteristics of ideological confrontation; the third stage, during the military government’s rule, the broadcasting technology was alienated into a tool to maintain the military government’s regime, and people in Myanmar and those in exile in Myanmar and exile organizations conducted resistance through underground radio stations; the fourth stage focuses on the competition for communication sovereignty in the digital era. Facing technological alienation and spectrum crises, Myanmar seeks technological autonomy and digital cultural independence, striving to reconstruct the autonomous development path of the broadcasting system in the process of decolonization and digital transformation. This evolution trajectory not only reveals the complex aspects of technological politics in post-colonial countries but also provides a typical sample for the research on media sovereignty in global southern countries.